2021
DOI: 10.1111/jgh.15705
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa Linn versus omeprazole in treatment of functional dyspepsia: A randomized, double‐blind, placebo‐controlled trial

Abstract: Background and Aims: Functional dyspepsia (FD) is a common problem in gastroenterology practice. The study aimed to compare the efficacy of Curcuma longa Linn versus omeprazole and placebo among patients diagnosed with FD. Methods: From November 2017 to November 2018, patients diagnosed with FD according to ROME IV criteria were enrolled. Patients were randomized into curcumin, omeprazole, or placebo groups. The Severity of Dyspepsia Assessment (SODA) was used to evaluate clinical effectiveness after 2 and 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…All studies (Abbas et al, 2017; Alt et al, 2017; Asif et al, 2015; Banerjee et al, 2021; Bommelaer et al, 2020; Brinkhaus et al, 2005; Bundy et al, 2004; Hanai et al, 2006; Kedia et al, 2017; Khonche et al, 2016; Koosirirat et al, 2010; Kositchaiwat et al, 1993; Lang et al, 2015; Lauche et al, 2016; Lopresti et al, 2021; Masoodi et al, 2018; Panahi et al, 2021; Portincasa et al, 2016; Sadeghi et al, 2019; Sawangroj et al, 2019; Singla et al, 2014; Sirijarugul, 2007; Sugimoto et al, 2020; Thamlikitkul et al, 1989; Van Dau et al, 1998; Yongwatana et al, 2022) were published between 1989 and 2021 and were conducted in Asia ( n = 13) (Asif et al, 2015; Banerjee et al, 2021; Hanai et al, 2006; Kedia et al, 2017; Koosirirat et al, 2010; Kositchaiwat et al, 1993; Sawangroj et al, 2019; Singla et al, 2014; Sirijarugul, 2007; Sugimoto et al, 2020; Thamlikitkul et al, 1989; Van Dau et al, 1998; Yongwatana et al, 2022), Europe ( n = 6) (Alt et al, 2017; Bommelaer et al, 2020; Brinkhaus et al, 2005; Bundy et al, 2004; Lauche et al, 2016; Portincasa et al, 2016), the Middle East ( n = 5) (Abbas et al, 2017; Khonche et al, 2016; Masoodi et al, 2018; Panahi et al, 2021; Sadeghi et al, 2019), and Australia ( n = 1) (Lopresti et al, 2021), with one multi‐country study (i.e., Israel, Hong Kong, and Cyprus) (Lang et al, 2015). Twenty‐five studies were randomized controlled trials (RCTs) (Abbas et al, 2017; Alt et al,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies (Abbas et al, 2017; Alt et al, 2017; Asif et al, 2015; Banerjee et al, 2021; Bommelaer et al, 2020; Brinkhaus et al, 2005; Bundy et al, 2004; Hanai et al, 2006; Kedia et al, 2017; Khonche et al, 2016; Koosirirat et al, 2010; Kositchaiwat et al, 1993; Lang et al, 2015; Lauche et al, 2016; Lopresti et al, 2021; Masoodi et al, 2018; Panahi et al, 2021; Portincasa et al, 2016; Sadeghi et al, 2019; Sawangroj et al, 2019; Singla et al, 2014; Sirijarugul, 2007; Sugimoto et al, 2020; Thamlikitkul et al, 1989; Van Dau et al, 1998; Yongwatana et al, 2022) were published between 1989 and 2021 and were conducted in Asia ( n = 13) (Asif et al, 2015; Banerjee et al, 2021; Hanai et al, 2006; Kedia et al, 2017; Koosirirat et al, 2010; Kositchaiwat et al, 1993; Sawangroj et al, 2019; Singla et al, 2014; Sirijarugul, 2007; Sugimoto et al, 2020; Thamlikitkul et al, 1989; Van Dau et al, 1998; Yongwatana et al, 2022), Europe ( n = 6) (Alt et al, 2017; Bommelaer et al, 2020; Brinkhaus et al, 2005; Bundy et al, 2004; Lauche et al, 2016; Portincasa et al, 2016), the Middle East ( n = 5) (Abbas et al, 2017; Khonche et al, 2016; Masoodi et al, 2018; Panahi et al, 2021; Sadeghi et al, 2019), and Australia ( n = 1) (Lopresti et al, 2021), with one multi‐country study (i.e., Israel, Hong Kong, and Cyprus) (Lang et al, 2015). Twenty‐five studies were randomized controlled trials (RCTs) (Abbas et al, 2017; Alt et al,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies were randomized controlled trials (RCTs) (Abbas et al, 2017; Alt et al, 2017; Asif et al, 2015; Banerjee et al, 2021; Bommelaer et al, 2020; Brinkhaus et al, 2005; Bundy et al, 2004; Hanai et al, 2006; Kedia et al, 2017; Khonche et al, 2016; Koosirirat et al, 2010; Kositchaiwat et al, 1993; Lang et al, 2015; Lopresti et al, 2021; Masoodi et al, 2018; Panahi et al, 2021; Portincasa et al, 2016; Sadeghi et al, 2019; Sawangroj et al, 2019; Singla et al, 2014; Sirijarugul, 2007; Sugimoto et al, 2020; Thamlikitkul et al, 1989; Van Dau et al, 1998; Yongwatana et al, 2022), and one was a randomized controlled crossover trial (Lauche et al, 2016). The patient conditions that were studied included IBD (UC or CD; n = 9 studies) (Banerjee et al, 2021; Bommelaer et al, 2020; Hanai et al, 2006; Kedia et al, 2017; Lang et al, 2015; Masoodi et al, 2018; Sadeghi et al, 2019; Singla et al, 2014; Sugimoto et al, 2020); IBS ( n = 5) (Alt et al, 2017; Brinkhaus et al, 2005; Bundy et al, 2004; Lauche et al, 2016; Portincasa et al, 2016); dyspepsia ( n = 5) (Panahi et al, 2021; Sawangroj et al, 2019; Sirijarugul, 2007; Thamlikitkul et al, 1989; Yongwatana et al, 2022); peptic, gastric, or duodenal ulcers ( n = 4) (Abbas et al, 2017; Khonche et al, 2016; Kositchaiwat et al, 1993; Van Dau et al, 1998); H. pylori infection ( n = 2) (Asif et al, 2015; Koosirirat et al, 2010); and “gastrointestinal complaints” (i.e., mild to moderately severe gastrointestinal discomfort, excluding IBDs and functional gastrointestinal d...…”
Section: Resultsmentioning
confidence: 99%
“…For example, capsaicin (derived from the peppers of the Capsicum genus) protected the gastric mucosa in healthy volunteers who took acetylsalicylic acid [ 57 ] and decreased the intensity of dyspeptic symptoms in patients with functional dyspepsia [ 58 ]. Curcumin, from Curcuma longa (turmeric), improved dyspeptic symptoms, improved quality of life, and provided a satisfactory equivalent to omeprazole in a double-blind, placebo-controlled trial in patients diagnosed with functional dyspepsia [ 59 ]. Patients treated with a Maytenus ilicifolia (espinheira-santa) extract for 28 days showed a significant improvement compared to the placebo group, with regard to the overall dyspeptic symptoms, and especially for symptoms of heartburn and gastralgia [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric was also shown to repair tendons and reduce associated pain in patients with tendinopathy. , A randomized, open-label clinical trial of curcumin (45 mg) intake as an oral film prior to alcohol consumption effectively reduced alcohol-induced hangover symptoms, such as dizziness, stomachache, and palpitations . A randomized, double-blind, placebo-controlled clinical trial of curcumin demonstrated reduced pain and severity scores in patients with chronic dyspepsia ( n = 132) . As an antiseptic solution, curcumin was shown to remarkably reduce redness, edema, ecchymosis, discharge, and approximation score and enhance healing compared to povidone-iodine solution in people who underwent episiotomy ( n = 120) .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…722 A randomized, double-blind, placebo-controlled clinical trial of curcumin demonstrated reduced pain and severity scores in patients with chronic dyspepsia (n = 132). 723 As an antiseptic solution, curcumin was shown to remarkably reduce redness, edema, ecchymosis, discharge, and approximation score and enhance healing compared to povidone-iodine solution in people who underwent episiotomy (n = 120). 724 Further, a double-blind, randomized clinical trial of curcumin cream (2%) applied for 10 days showed remarkably reduced episiotomy pain and increased wound healing.…”
Section: Turmeric and Curcumin In Inheritedmentioning
confidence: 99%